Blast Vibration Damage Potential in a Residential Structure from Intentional Full-Scale Nearfield Quarry Blasting - Daykin Schnell; Josh Calnan; Zach Agioutantis (International Society of Explosives Engineers, 2026)
Damage complaints are a common occurrence related to blasting activities, specifically when blasting operations occur near residential areas. These complaints are often associated with ground vibrations from blasting. It is important for blasters and engineers to understand the potential for ground vibrations to damage residential structures to properly design blasts and appropriately address any damage complaints that arise. A review of the most recent studies of blast vibration damage thresholds for residential structures is conducted to provide a baseline understanding of blast damage potential and mechanisms. Gaps in research and understanding blast vibration damage potential are identified. Research in further understanding damage potential is presented and focuses on studying the impact of high-range ground vibrations generated from full-scale, nearfield ground vibrations from blasting on a residential structure. Specific impacts of the high-range ground vibrations reviewed as part of this research include damage to the block wall basement, global strain, rotational forces, crack generation, and crack extension in a residential structure. Planning and methodology for intentional full-scale, nearfield blasting at a limestone quarry within close proximity to a residential structure owned by the quarry are presented. Conclusions discuss the objectives and optimized layout of the ongoing data collection for the proposed research and analysis. Future potential work related to further understanding blast damage mechanisms and thresholds are also discussed.